Integrasi Multimodal dalam Pembelajaran BIPA Berbasis Kearifan Lokal Batik Gedog Tuban untuk Penguatan Keterampilan Berbahasa: Studi Literatur - Rofi Atin Khanifah; Anas Ahmadi; Agusniar Dian Savitri (Paedagogie, 2026)
Indonesian Language Learning for Foreign Speakers (BIPA) is not only focused on mastering linguistic aspects but also on understanding culture as the context for language use. This study aims to examine multimodal integration in BIPA learning based on the local wisdom of Tuban Gedog Batik to strengthen learners’ language skills. This study employs a literature review method with a descriptive qualitative approach. Data were obtained from scientific journal articles accessed via Google Scholar and analyzed using content analysis techniques. The findings indicate that Tuban Gedog Batik possesses strong potential as an authentic learning resource due to its rich historical, philosophical, and socio-cultural values. Furthermore, the characteristics of Tuban Gedog Batik allow for the development of learning materials in various modes of representation, such as text, visual, audio, and audiovisual, in accordance with the principles of multimodal learning. Integrating Tuban Gedog Batik into BIPA instruction has the potential to enhance learners’ language proficiency while simultaneously strengthening their intercultural competence. The uniqueness of this study lies in the integration of a multimodal approach, audiovisual media, and the local wisdom of Tuban Gedog Batik into a single conceptual model for BIPA instruction. Furthermore, it is suitable for intermediate to advanced BIPA learners (levels 4–6) as it supports the development of reading, listening, speaking, and writing skills in a contextual manner. Thus, this study contributes to the development of culture-based and multimodal BIPA learning as an effort to support the internationalization of the Indonesian language.